2020
DOI: 10.3389/fimmu.2020.591139
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Specific Antibody, Cetuximab, Enhances the In Situ Vaccine Effect of Radiation in Immunologically Cold Head and Neck Squamous Cell Carcinoma

Abstract: In head and neck squamous cell carcinoma (HNSCC) tumors that over-expresses huEGFR, the anti-EGFR antibody, cetuximab, antagonizes tumor cell viability and sensitizes to radiation therapy. However, the immunologic interactions between cetuximab and radiation therapy are not well understood. We transduced two syngeneic murine HNSCC tumor cell lines to express human EGFR (MOC1- and MOC2-huEGFR) in order to facilitate evaluation of the immunologic interactions between radiation and cetuximab. Cetuximab was capabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…From the B78 melanoma re-challenged mice, we collected splenocytes and co-cultured them with B16 melanoma cells that are parental to B78 and share common TAAs (Fig. 5g ) 7 , 47 . Using flow cytometry on these B16-co-cultured splenocytes, we observed increased levels of early activation marker, CD69 + , on both CD4 + and CD8 + T cells from mice rendered disease-free by PIC + RT + anti-CTLA-4, as compared to B16-co-cultured splenocytes from naïve control mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…From the B78 melanoma re-challenged mice, we collected splenocytes and co-cultured them with B16 melanoma cells that are parental to B78 and share common TAAs (Fig. 5g ) 7 , 47 . Using flow cytometry on these B16-co-cultured splenocytes, we observed increased levels of early activation marker, CD69 + , on both CD4 + and CD8 + T cells from mice rendered disease-free by PIC + RT + anti-CTLA-4, as compared to B16-co-cultured splenocytes from naïve control mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several lines of evidence support a crucial role for NK cells in the CD16-dependent therapeutic efficacy of tumor-targeting mAbs. The composition and quality of tumorinfiltrating immune compartment are modified upon mAb treatment; in particular, several studies reported that intratumoral and circulating NK cell numbers increase upon tumor-targeting mAb-based combination regimens and that this correlated with favorable outcome [95][96][97][98][99]. Moreover, the observation that anti-lymphoma activity of rituximab was improved in the presence of anti-KIR mAb (IPH2102-lirilumab), in a syngeneic murine lymphoma model [100], and the evidence that NKG2A blockade by specific mAb (IPH2201monalizumab) potentiated cetuximab-dependent NK antitumor functions [101], together with the observation that Treg-mediated suppression of ADCC correlates with a lower clinical efficacy in cetuximab-treated HNSCC patients [102], further stress the concept that CD16-dependent NK cell effector functions heavily contribute to explain the therapeutic efficacy of tumor-targeting mAbs.…”
Section: Cd16 As a Relevant Receptor For Tumor-targeting Mab Therapeutic Efficacy: The Contribution Of Nk Cellsmentioning
confidence: 99%
“…Flow cytometry was performed as previously described, 32 using fluorescent beads (UltraComp Beads eBeads, 176 Invitrogen, #01-2222-42) to determine compensation and fluorescence minus one methodology to determine gating ( online supplemental figure S2 ). For in vivo analysis, tumors and tumor draining lymph nodes were harvested and gently dissociated.…”
Section: Methodsmentioning
confidence: 99%